Los jóvenes adoran el ocio digital: un estudio cuantitativo sobre los jóvenes universitarios y el consumo // The young people embellish their digital leisure: A quantitative study on university students and consumption - Tardivo, Giuliano; Suárez-Vergne, Álvaro; Díaz Cano, Eduardo (Espacio Abierto, 2019)
ResumenEl objetivo es conocer cuáles son las marcas favoritas de los jóvenes universitarios madrileños, qué relación tienen con esas marcas y cómo les ha afectado la crisis económica. Se aplicó una encuesta entre 591 estudiantes de tres universidades públicas de Madrid.. Los resultados demuestran que las marcas relacionadas con el ocio digital son las preferidas y que el perfil del consumidor ostentoso e inflexible – con gran apego hacia sus marcas favoritas – se ha ido reduciendo como consecuencia de la crisis.AbstractThe aims of this work are to know, which the favorite brands of the university students of Madrid are, how university students of Madrid do relate to his favorite brands, and how the economic crisis has affected them. We have carried out a survey in three public universities of Madrid, for a total of 591 survey respondent students. The results show that the brands related to the digital leisure are the favorites of the university young students of Madrid and that the profile of the conspicuous and inflexible consumers – those who love their favorite brands – has been diminishing as a consequence of the economic crisis.